Study on Performance of the Food and Beverage (F&B) Service Employee - Petra Ugahari Ayu S (Soegijapranata Catholic University, 2019)
A favourable service quality depends on the individual employee performance. The better the employee performance, the more favourable the service quality. This study underlined the Food and Beverage (FB) service employee performance of CC Club and the factors influence it which cover job stress, leadership style and training. A regression and significance tests are used to see relationship of employee performance to job stress, leadership style and training. The study discovered that the performance of FB service employee of CC Club is 84.4% affected by job stress, leadership style and training. These variables have statistically significant effect partially and simultaneously on the performance. The change in one or more variables will reflect on the overall performance of the employees